How Far Have We Reached in European Cooperation in Civil Matters? A View on European Enforcement - Nicolae-Horia Tit (CES Working Papers, 2015)
The EU judicial cooperation in civil matters system was developed following the needs of member states to achieve a common goal, which is to create a space of mutual recognition of judgements and distribute the juridical effects of the order created under one jurisdiction thru out the entire European space. One of the main pillars of this system is the creation of European Enforcement Orders, judgements or other titles enforceable in a member state without prior recognition of declaration of enforceability. This system has been developed other the years, starting with the European Enforcement Order for uncontested claims, continuing with the European Order for Payment procedure and European Small Claims procedure, and reaching its peak in Regulation (EU) 1215/2012. By virtue of this Regulation, entered into force in January 2015, a judgment given in a Member State which is enforceable in that Member State shall be enforceable in the other Member States without any declaration of enforceability being required (art. 39). The article analyses the evolution of EU regulation regarding the enforceability of foreign judgements and the system created under Regulation (EU) 1215/2012, given its importance for the judicial cooperation in civil matters and its impact on the legislation of member stated. Also, a brief analysis of the provisions of the new Romanian civil procedure Code is made, given its amendments by Law no. 138/2014.
Keywords: K33; 330; judgement; enforcement; European enforcement order; claim